Teachers’ Strategies to Improve Students’ Self-Confidence in Speaking: A Study at Two Vocational Schools in Central Borneo - Listyani - Listyani; Lavani Satya Kristie (UIN Salatiga, 2018)
Speaking become one of the important skills among other skills such as listening, reading and writing. However, some students felt not confident to deliver words or sentences in English. The purpose of this study was to find teachers’ strategies to improve students’ self confidence in speaking at SMK 1 and SMK 2 in Tamiang Layang. This study used qualitative study with two instruments which are interview and observation. The participants were four teachers from two different schools which are SMK 1 and SMK 2. Based on the finding, there was found four strategies that the four teachers used in speaking class activity. Those strategies are role-play, small group discussion, storytelling, and songs. These strategies were very helpful to encourage students’ self confidence in speaking, because each strategy giving a chance for students to pratice speaking. Besides that, the advantages that students got from those, help students increase their vocabulary and pronunciation, build an interaction between passive and active students, and make the class more fun and not boring.Keywords: Speaking, self-confidence, teachers’ strategies.